Development of Learning Tools: Parscel Application in Accounting Course - Syarifudin, Moh.; Wahyudhi, Imam; Alwya Syarif, Siti (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The issues faced by students at IAIN Fattahul Muluk Papua in Shariah academic learning include low grades in courses containing materials on Shariah contract calculations, such as Islamic financial accounting and banking practices, due to the diverse nature of Shariah contracts. The research employed the ADDIE development model for its design. In the development phase, the sustainability aspect of the application takes center stage. Interactive features, particularly in the Shariah contract calculator menu, serve as key elements to ensure user engagement. The integration of multimedia elements, including video tutorials and calculation simulations, enriches the learning experience. During the evaluation phase, updates based on user feedback are implemented to address potential shortcomings, supporting the transformation of the Parscel Application into an effective Shariah academic learning resource. In the context of instructional media feasibility, involving respondents from various backgrounds, including students, enhances the representativeness of evaluation results. Strengthening evaluation aspects, such as incorporating feedback mechanisms in each module, is implemented to enhance understanding of Shariah contract concepts. With this approach, the Parscel Application continues to be enhanced in accordance with quality standards and student learning needs